2017
DOI: 10.1093/neuros/nyx423
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Chordoma: A New Preoperative Grading System

Abstract: BACKGROUNDChordomas are rare but challenging neoplasms involving the skull base. A preoperative grading system will be useful to identify both areas for treatment and risk factors, and correlate to the degree of resection, complications, and recurrence.OBJECTIVETo propose a new grading system for cranial chordomas designed by the senior author. Its purpose is to enable comparison of different tumors with a similar pathology to clivus chordoma, and statistically correlate with postoperative outcomes.METHODSThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Clival chordoma is a rare, primary bone tumor arising from notochord remnants 17 , 18 . It can infiltrate various areas of the skull base such as the upper, middle and lower clivus, cavernous sinus, petrous bone, and upper cervical spine with or without intradural invasion 13 . Complete surgical resection is a challenge considering the deep-seated location of the tumor and the close proximity to critical neurovascular structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clival chordoma is a rare, primary bone tumor arising from notochord remnants 17 , 18 . It can infiltrate various areas of the skull base such as the upper, middle and lower clivus, cavernous sinus, petrous bone, and upper cervical spine with or without intradural invasion 13 . Complete surgical resection is a challenge considering the deep-seated location of the tumor and the close proximity to critical neurovascular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated prognostic factors of clival chordoma, but the understanding of the disease is still limited due to its rarity and cancer biology. Previous studies have revealed that tumor size, location, and extent of resection (EOR) are associated with overall survival (OS) and progression-free survival (PFS) in clival chordoma 4 , 13 , 14 . However, there are still no reliable factors that could predict the behavior of the tumor before treatment begins.…”
Section: Introductionmentioning
confidence: 99%
“…CSF leakage and cranial nerve injury were the main complications in prior studies [17,14,6]. Bene ting mainly from the application of vascularized nasoseptal aps [17,7], CSF leakage was low in our group (3.9%).…”
Section: Surgical Complications and Treatmentsmentioning
confidence: 47%
“…This may be explained by our previous nding that most children with SBCs had these tumors in the lower clivus and cranio-cervical junction area [4]. Tumors in the lower clivus have the lowest GTR rate [14,17,6,4]. Not surprisingly, history of surgery, large tumor volume and tumor location are independent risk factors for GTR, as supported by previous studies [30,14,17,26,7].…”
Section: Risk Factors Reducing the Chances Of Gtrmentioning
confidence: 62%
See 1 more Smart Citation